Analisis Tematik Strategi Teknologi Informasi Dalam Kepemimpinan Sektor Keuangan - Ardiansyah, Tedy; Dariansyah, Deddy; Purwaningsih, Dewi (Faculty of Economic and Business Wijaya Kusuma Surabaya University, 2025)
The digital transformation of Indonesia's financial sector has amplified the strategic role of Information Technology (IT) in supporting efficiency, innovation, and regulatory compliance. However, academic studies thematically exploring IT leaders' strategies and challenges in local contexts remain limited. This study aims to identify similarities and differences in the IT strategies implemented by six technology leaders from the Indonesian banking, financing, and life insurance industries. The method employs a qualitative thematic analysis using narrative quotes from informants published in the August 2025 edition of Marketing Magazine. The findings reveal that system integration, operational efficiency, and regulation are common areas of focus. Conversely, approaches to innovation, user experience, and infrastructure modernization show significant variation across informants, indicating that IT strategies in the Indonesian financial sector are contextual and heterogeneous. The novelty of this research lies in the thematic mapping based on quotations, which reveals the dynamics of local technology leadership and opens space for developing more adaptive IT leadership theories